Encouragement of Women's Employee Performance Based on o Modern Working Environment and Work Discipline on The Store Cashier and Sales Promotion Girl - Mustikaningrum Hidayati; Honorata Ratnawati Dwi Putranti; Muchamad Ardiansyah (Media Ekonomi dan Manajemen, 2019)
Large cities are developing followed by the development of shops that are managed in a modern way. This condition opens opportunities for female employees to get jobs as sales promotion girls (SPG) and cashiers. SPG and cashiers as direct services to consumers, so that attention needs to be paid to the work environment and work discipline because these conditions can support services to consumers. This study aims to analyze the influence of the modern work environment and work discipline on performance, as well as driving indicators of the performance of female cashier and SPG employees in Semarang City. The population of this study is the SPG and the women's cashier of modern shops in Semarang City. This study uses technical snowball sampling and purposive random sampling with a total of 100 respondents. Distribution of questionnaires using google.docs (internet) on the link https://goo.gl/forms/ lxm7HfLSX4huuxwt1. The results of this study, there is a positive and significant relationship between the modern work environment and work discipline. The drivers of women's performance are explained by findings. Modern environments such as Wi-Fi and pantry are things that can improve women's performance.Keywords: Modern Work Environment, work discipline, SPG (Sales Promotion Girl) and CashierKota-kota besar berkembang diikuti pula berkembangnya pertokoan yang di kelola secara modern.Kondisi ini membuka peluang bagi karyawan perempuan untuk mendapatkan lapangan pekerjaan sebagai sales promotion girl (SPG) dan kasir. SPG dan kasir sebagai pelayanan langsung kepada konsumen, sehingga perlu perhatian pada lingkungan kerja dan disiplin kerja, karena kondisi ini dapat menunjang pelayanan kepada konsumen.Penelitian ini bertujuan menganalisis tentang pengaruh lingkungan kerja modern dan disiplin kerja terhadap kinerja, serta indikator-indikator pendorong kinerja pegawai Kasir dan SPG perempuan di Kota semarang. Populasi penelitian ini adalah SPG dan kasir perempuan pertokoaan modern di Kota semarang, Penelitian ini menggunakan teknis snowball sampling dan purposive random sampling dengan jumlah 100 responden. Penyebaran kuesioner menggunakan google.docs (internet) pada link https://goo.gl/forms/ lxm7HfLSX4huuxwt1. Hasil penelitian ini, ada hubungan positif dan signifikan antara lingkungan kerja modern dan disiplin kerja.Faktor pendorong kinerja perempuan di jelaskan dengan temuan lingkungan modern seperti Wi-Fi dan pantry (dapur kecil) menjadi hal yang dapat meningkatkan kinerja perempuan.Kata kunci : Lingkungan Kerja modern, disiplin kerja, SPG (Sales Promotion Girl) dan Kasir